A method for evaluating the bond behavior and anchorage length of embedded carbon yarn in the cementitious matrix. (20th September 2020) - Zhu, Miaochang; Zhu, Ji-Hua; Ueda, Tamon; Su, Meini; Xing, Feng
Highlights: The trilinear bond slip relationship for carbon yarn embedded in matrices can be obtained. Various matrices can affect the bond slip relationship of the embedded carbon yarn. The anchorage length [1–55] can be evaluated based on the geometries and material properties. The carbon yarn's anchorage length is most influenced by the local bond strength. Abstract: This paper presents a method for evaluating the bond behavior of a single carbon yarn embedded in the cementitious matrix. Pullout tests were carried out in which the carbon yarn was progressively pulled out of the matrix. All the pullout specimens with a nominal bond length of 15 mm showed a similar pullout curve that was characterized by an initial ascending part and a descending part followed by a slowly decreasing part, along with the same failure mode due to the slippage of the carbon yarn through the matrix. The proposed method was used to evaluate bond parameters in the trilinear bond-slip relationship, which has been demonstrated to be applicable for describing the carbon yarn-cementitious matrix interface. The reliability of the evaluation method has been substantiated by achieving good agreement between the analytical and experimental results obtained from a wide range of pullout tests. An analytical approach was proposed to directly calculate the anchorage length of all the pullout specimens based on the evaluated trilinear bond-slip relationships, and the calculations were verified against the numerical results. In addition, a parametric study was carried out to investigate the effects of the bond parameters on the carbon yarn's anchorage length and showed that the anchorage length was influenced most by the local bond strength.